Hydrogen-rich water treatment improves fresh-cut Gastrodia elata quality by regulating reactive oxygen species metabolism and energy metabolism during low temperature storage - Dong, Boyu; Zhu, Dequan; Yao, Qiuping; Da, Fangfang; Chen, Yulong; Ding, Xiaochun (Frontiers in Sustainable Food Systems, 2023)
The application of hydrogen-rich water (HRW) can extend the shelf life of fruits and vegetables. This study aims to investigate the effects of HRW on the quality of fresh-cut Gastrodia elata during low-temperature (4°C) storage. The results indicate that HRW treatment inhibited the decrease in weight loss and the increase in respiration rate, and also slowed down the decrease in total acidity and total soluble solids. HRW treatment could reduce the generation of superoxide anions and hydrogen peroxide, enhance the activity and expression of antioxidant-related enzymes such as superoxide dismutase, catalase, ascorbate peroxidase, glutathione reductase, monodehydroascorbate reductase, and dehydroascorbate reductase, and increase the content of non-enzymatic antioxidant substances, ascorbic acid and glutathione, while decreasing the activity and expression of peroxidase and polyphenol oxidase. Furthermore, HRW treatment not only inhibited the reduction in ADP and ATP content and energy charge but also attenuated the increase in AMP content. It also slowed down the decrease in the activities of H+-ATPase, succinate dehydrogenase, Ca2+-ATPase, and cytochrome C oxidase. In conclusion, these results demonstrate that HRW treatment enhances the energy levels and effectively mitigates oxidative damage, thereby preserving postharvest quality of fresh-cut G. elata.